Subgroup analysis based on cytogenetic risk in patients with relapsed or refractory multiple myeloma in the CANDOR study. (24th May 2022) - Landgren, Ola; Weisel, Katja; Rosinol, Laura; Touzeau, Cyrille; Turgut, Mehmet; Hajek, Roman; Mollee, Peter; Kim, Jin Seok; Shu, Natalie; Hu, Xuguang; Li, Chuang; Usmani, Saad Z.
Abstract: CANDOR compared the safety/efficacy of carfilzomib with dexamethasone and daratumumab (KdD) to carfilzomib with dexamethasone (Kd) in adults with relapsed/refractory multiple myeloma (RRMM). This CANDOR subgroup analysis evaluated outcomes based on cytogenetic risk. Overall response rates (KdD vs. Kd) were 81% versus 56% in high‐risk and 87% versus 79% in standard‐risk groups. Median progression‐free survival was 11.2 versus 7.4 months in high‐risk (hazard ratio, 0.56 [95% CI, 0.34, 0.93]) and not reached versus 16.6 months in standard‐risk groups (0.56 [95% CI, 0.39, 0.80]). These data support the efficacy of KdD in RRMM treatment, including in patients with high‐risk cytogenetics.